Health impact of river water pollution in Malaysia - Rafia, Afroz; Rahman, Mohammed Ataur (Institute of Advanced Science Extension (IASE), 2017)
Water pollution is a severe problem in Malaysia and has an adverse impact on the sustainability of water resources. Not only has that but also affected plants and living organisms, the health of the population and the economy. This study reviews the state of river water quality and sources of river water pollution in Malaysia. The Department of Environment program continued monitoring of the quality of river water in 2014 to determine the status of water quality of the river and to detect changes in water quality of the river. They found that 52% of the river was found to be clean, 39% slightly contaminated and 9% contaminated. The number of the polluted river is declined over the period of time. They also observed that beverage industries are the major source of pollution in this country. This paper reviews the environmental policy related to water pollution and studies related to water pollution and health impacts.